1Kata mobile game application / Muhammad Ilham Amri…[et al.] - Amri, Muhammad Ilham; Ismail, Mohamad Farid; Nordin, Mohammad Hanif; Abd Aziz, Ahmad Kamal (2012)
Nowadays, there is a thousand of application or games that have been developed in android platform. As a result, the demands of user to play a variation of game have been increase slightly. In this project we propose to develop an education game which is crossword game. However, a lot of crossword games are already in market but the differences of our game from others are it is play in Bahasa Melayu. Therefore to make sure our game is more interactive than others we will collecting a thousand frequently used Bahasa Melayu word into the database and provide the rules, ensure the game be able to retrieve the correct word that has been insert into database table. In conclusion, this game will give a lot of benefit to people especially student to improve their Bahasa Melayu vocabulary and critical thinking skills.